Experimental Study of an Air Lift Pump - Abou Taleb, F. S.; Al-jarrah, J. A. (Engineering, Technology & Applied Science Research, 2017)
In this investigation the effect of submergence ratio and air jacket on the performance of the air lift pump has been studied. Three types of air jackets in addition to five levels of submergence ratios were used. Each air jacket has a number of drilled holes distributed uniformly at the perimeter of the inside pipe, where the total area of drilled holes was kept constant. It has been found that the water flux increases as the submergence ratio increased. Also it was found that the minimum air flux required to start discharging water from the pump decreases as the submergence ratio increases. Air jacket with a hole of 4 mm diameter, resulted the highest performance for the air lift pump.